Efecto de la asociación amiodarona-enalapril sobre la electrofisiología y función sistodiastólica en la cardiomiopatía dilatada canina - Buzzano, Orlando Omar (2019)
This research prioritize the interest to evaluate and interrelate the different data\nobtained from the twenty canine patients with primary DCM with which we have worked. In this context, we conducted different studies to determine if changes in cardiac structure, functions or electrical condition were present and, if so, to quantify them to check the therapeutic effects of amiodarone hydrochloride (A) and its combination with\nenalapril maleate (A + E).\nPatients with primary DCM included were separated into two groups (G); (G1-\nDCM and G2-DCM). According to the therapeutic protocols used, the mentioned groups\nreceived the definitive denomination of G1-DCM + A and G2-DCM A + E respectively. In G1-DCM + A, variables related to electrophysiological alterations were controlled or improved. This effect is attributed to the properties of amiodarone hydrochloride.\nThe same did not happen with the variables related to structural and functional\nchanges, since the progress of the primary DCM, in general, continued to deteriorate them.\nThrough the different cardiological controls carried out, we observed that the most important results occurred in G2-DCM A + E. In this group, altered electrophysiological\nvariables also improved, as well as the functional and anatomical aspects, fact that we attribute this effect to enalapril maleate.\nIn addition, the modifications that were found in the structure variables as well as in the systolic-diastolic function of the left ventricle (LV) were relevant in G2-DCM A + E. These changes, in general, showed better pump function and control of ventricular dysrhythmia.\nThe comparative aspects in all cases refer to intra-group pre and post-treatment\nvalues. We believe that we would have achieved better results in some of the variables studied, prolonging the therapeutic period.\nTo explain more clearly what happened in our investigation, we grouped the twenty-nine variables and the two indices, with which we work, in the following way: 1.- Evaluation of the LV systolic function.\nTo study the changes before and after treatment of this function, we have analyzed in both groups, the evolution of eighteen variables. These are detailed in materials and method and are analyzed in results. As we mentioned, this function improved in G2-DCM A + E, being: 1.- A decrease in the values of: SSPE, DDVI, DSVI, MMVI, IMMVI, VDF, VSF, PPE, and IE (the latter from both windows). The VacCf revealed a tendency to reduce the shortening time, but there were no significant differences.2.- An increase of: FA%, FAm%, FEy%, Vp. Ao, the PE, and the S-tissue wave.3.- We have not found modifications in the RWT.\nIt is important to mention that, the AI continued to increase its dimensions in the groups treated; consequently, we suppose that the enalapril maleate did not reversereform this chamber, but did so in the VI, in which the decrease in both diameters was\nobserved. With respect to the two indices studied (Tei and Weissler) it was observed that at the beginning of the investigation both were increased in the two groups (G1-DCM and G2-DCM). At the end of the experience, these indices were reduced in the G2-DCM A + E, indicating an improvement in systodiastolic and systolic function, respectively.\n2.- Evaluation of the LV diastolic function:\nThis function has been studied by jointly analyzing five variables. We have\nverified by transmitral flow Doppler that the G1 presented characteristics of a restrictive pattern, indicative of diastolic alteration. The same did not happen in the G2-DCM A + E, in which the decrease of: Vp was observed of the E wave and the E/A ratio, as well as the increase of the Deceleration Time of E wave, of the Vp. of wave A and IVRT. 3.- Non-invasive electrophysiological evaluation. We have analyzed and categorized six electrophysiological variables as follows:\n3.1.- Evaluation of ventricular repolarization alterations: 3.1.1.- The IQT lasted approximately 10% in both groups. Likewise, in all canines with untreated DCM, said QTI was lower because of the compensatory increase of the HR. 3.1.2.- The TDR (IT-p-e) was reduced in the two groups treated with amiodarone. The opposite effect occurred in the two groups prior to treatment.\n3.1.3.- We have not found MAlt.T in any of the groups investigated. 3.2.- Evaluation of the Autonomic Nervous System: 3.2.1.- HRV in the SDNN component decreased in G1-DCM and G2-DCM due\nto the increase in HR. In both treated groups (G1-DCM + A and G2-DCM A + E) we observed a higher value of SDNN. 3.2.2.- The TO% parameter of the THR was negative in the G1-DCM and G2-DCM and positive in both the G1-DCM + A and the G2-DCM A + E. Amiodarone increased the RR cycle length after CPV and did not do it in the same way in the preCPV sequence. The TS mseg / RR was greater than the normality reference and decreased in the two treated groups. 3.3.- Evaluation of the ST segment: 3.3.1. - In none of the canine groups with DCM (pretreated and subsequently treated) was the existence of supra or underside of the ST segment significant.\nWe believe that both the hypothesis and the objectives set out in this investigation have been met. Likewise, we have made our results known through various scientific\npublications with arbitration\nA fundamental aspect of the present investigation is that although the treatment\nused does not cure the disease, it has made it possible to improve the quality of life of the patients studied and to prolong their survival.